Reputasi Auditor Sebagai Pemoderasi Pengaruh Informasi Keuangan dalam Prospektus Pada Tingkat Underpricing Penawaran Saham Perdana - Permadi, Pande Kadek Ary Raditya; Yasa, Gerianta Wirawan (E-Jurnal Akuntansi; Vol 21 No 3 (2017)DO - 10.24843/EJA.2017.v21.i03.p10, 2017)
Capital market is a place where public are able to bid and ask of shares. Capital market serves as a source of financing and investing, both in the business or investor. As we know about, capital market is divided into primary market and secondary market. Primary market is the place for a new listing company offering its shares, meanwhile secondary market is the place to offers its shares after initial offerings in primary market. Companies that will go public usually publish their prospectus which contains many information that really important for any investor in making a good investment decisions and not misleading in future.The purpose of this research is to know the auditor's reputation as a moderator of the influence of size, return on assets and financial leverage at the level of underpricing initial public offering in Indonesia Stock Exchange. This study was conducted on companies that conducted an IPO in 2012-2014. Total population are 77 companies. There were 63 sample companies using non-probability sampling method with purposive sampling technique. Data collection methods with nonparticipant observation. Data analysis technique used is Moderated Regression Analysis. The result of data analysis shows that size and return on assets have negative effect on underpricing level, while financial leverage have positive effect on underpricing level. The auditor's reputation weakens, the negative effect of return on assets and the positive effect of financial leverage on the underpricing level, while the auditor's reputation is not able to moderate the effect of size on the underpricing level.